2016
DOI: 10.1155/2016/9565364
|View full text |Cite
|
Sign up to set email alerts
|

Detection of the Single-Session Complete Ablation Rate by Contrast-Enhanced Ultrasound during Ultrasound-Guided Laser Ablation for Benign Thyroid Nodules: A Prospective Study

Abstract: This study aimed to investigate the single-session complete ablation rate of ultrasound-guided percutaneous laser ablation (LA) for benign thyroid nodules. LA was performed in 90 patients with 118 benign thyroid nodules. Contrast-enhanced ultrasound (CEUS) was used to evaluate complete nodule ablation one day after ablation. Thyroid nodule volumes, thyroid functions, clinical symptoms and complications were evaluated 1, 3, 6, 12, and 18 months after ablation. Results showed that all benign thyroid nodules succ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 26 publications
1
17
0
Order By: Relevance
“…During follow-up, simple B-mode US nodule evaluation is generally not adequate to distinguish between the still vital part of the nodule and the area of ablated tissue. So, the use of other modalities such as color-Doppler or contrast-enhanced US may be considered for the detection of the still vital part of the treated nodule [4,52,59].…”
Section: Statementsmentioning
confidence: 99%
“…During follow-up, simple B-mode US nodule evaluation is generally not adequate to distinguish between the still vital part of the nodule and the area of ablated tissue. So, the use of other modalities such as color-Doppler or contrast-enhanced US may be considered for the detection of the still vital part of the treated nodule [4,52,59].…”
Section: Statementsmentioning
confidence: 99%
“…Ma et al [ 48 ] evaluated the single-session complete ablation rate of US-guided percutaneous laser ablations for benign thyroid nodules, and found that all nodule volumes significantly decreased from the original size at 1 day after ablation.…”
Section: Ceus Evaluation Of Us-guided Laser Ablation For Benign Thyromentioning
confidence: 99%
“…However, some typically benign thyroid nodules may spontaneously shrink, decreasing in size, while progressively showing morphologic changes that could be mistaken for malignant features on US examinations over time . This process involving morphologic changes, known as thyroid nodule mummification, may occur spontaneously over time or may result from thyroid nodule fine‐needle aspiration (FNA) or percutaneous ethanol or laser ablation . Therefore, it is important to differentiate mummified thyroid nodules from thyroid carcinomas in avoid unnecessary thyroid surgery.…”
mentioning
confidence: 99%
“…fine-needle aspiration (FNA) or percutaneous ethanol or laser ablation. [4][5][6][7] Therefore, it is important to differentiate mummified thyroid nodules from thyroid carcinomas in avoid unnecessary thyroid surgery.…”
mentioning
confidence: 99%